The effect of plastic bag containment of the head on the rate and pattern of decomposition. (April 2020) - Weger, Maxx; Cross, Peter; Cunliffe, Rachel
Abstract: Plastic bag suffocation has been reported in cases of homicide, suicide, and accidental death, with an increase in numbers of suicide and accidental deaths. Though case reports are abundant, decomposition studies have not been performed. This study utilised 20 Sus scrofa domesticus to quantify the effect of a plastic bag covering the head on the rate and pattern of decomposition. A sample group of ten carcasses had plastic bags placed over the heads, with another ten carcasses acting as a control group, without a head covering. The carcasses were placed in an open field to decompose. Over the course of 52 days, data were collected bi-weekly on the rate and pattern of decomposition. The results show that a plastic bag covering the head of a carcass has an overall decreased effect on the rate of decomposition, compared to the control group. The decomposition pattern of head > trunk > limb in decreasing decomposition rate was not affected by the plastic bag; however, in comparison to the control group, the decomposition of the head and trunk regions differed significantly, while the limbs stayed unaffected. The heads of the sample group showed a decrease in decomposition rate, while the trunks showed an increase. This was deemed due to an increase in insect activity at the trunk and a decrease in activity at the head. An altered PMI calculation is provided. Highlights: Covering the head has an overall decreased effect on the rate of decomposition. Insect activity is diverted from the head to the trunk and limbs. Post-mortem interval calculation requires adaptation, due to covering effect.